Evaluating the relationship between sources of environmental exposure in pregnant women and dimethoate concentrations in amniotic fluid - عيسى, البتول; فاضل, إقبال; ميهوب, فلورا; صالح, حسن (Latakia University Journal -Biological Sciences Series, 2024)
190 tripartite samples (father - mother - newborn) participated in the study, and it lasted for a year from May 2022 until April 2023 at Tishreen University Hospital in Latakia Governorate. This study included calibrating the dimethoate pesticide residues in the amniotic fluid using HPLC technology according to the established analysis conditions, and using the SPSS program with the aim of finding bilateral relationships between the sources of environmental exposure of pregnant mothers to the dimethoate pesticide and the concentrations of its residues in the amniotic fluid. The concentrations of dimethoate pesticide residues varied greatly among the studied samples, This study found basic determinants that contributed to the high levels of dimethoate for pregnant mothers who live in the countryside, or near greenhouses or tobacco growing fields, or near Fruit tree orchards, vegetable growing fields, or rose and ornamental tree nurseries, compared to mothers who do not reside near these places.